A tunable transition metal dichalcogenide entangled photon-pair source - Maximilian A. Weissflog; Anna Fedotova; Yilin Tang; Elkin A. Santos; Benjamin Laudert; Saniya Shinde; Fatemeh Abtahi; Mina Afsharnia; Inmaculada Pérez Pérez; Sebastian Ritter; Hao Qin; Jiri Janousek; et al. (Nature Communications, 2024)
Abstract Entangled photon-pair sources are at the core of quantum applications like quantum key distribution, sensing, and imaging. Operation in space-limited and adverse environments such as in satellite-based and mobile communication requires robust entanglement sources with minimal size and weight requirements. Here, we meet this challenge by realizing a cubic micrometer scale entangled photon-pair source in a 3R-stacked transition metal dichalcogenide crystal. Its crystal symmetry enables the generation of polarization-entangled Bell states without additional components and provides tunability by simple control of the pump polarization. Remarkably, generation rate and state tuning are decoupled, leading to equal generation efficiency and no loss of entanglement. Combining transition metal dichalcogenides with monolithic cavities and integrated photonic circuitry or using quasi-phasematching opens the gate towards ultrasmall and scalable quantum devices.